Islam dan Film Horor: Membentengi Individu dengan Keimanan dalam Film Qodrat - Munirul Hakim, Ahmad (Journal of Religion and Film, 2023)
This research attempts to look at the Islamic side in horror films which are often misused, including in the film entitled Qodrat. The film Qodrat is a horror film that tells the story of the rukiah ability of a ustadz in eliminating irregularities by a ustadz in a village. This research was conducted using a content analysis approach. Look directly at the text in the Qodrat film to obtain relevant data. The results of this research show that Islam in the film Qodrat is represented by two characters or actors, namely a cleric named Jakfar who deviates from Islamic teachings and a cleric named Qodrat who firmly stands on Islamic teachings. Jakfar is a deviant from Islamic teachings behind religious clothes, Islamic boarding schools and the label of ustadz to take material advantage by making alliances with jinns to possess village residents. He received compensation that a cleric should not receive in curing people from being possessed by jinns and demons through rukiah. On the other hand, Qodrat is a religious figure who upholds Islamic beliefs in living his life and is not thirsty for material things. He believes that rukiyah is charity and it is their duty as religious leaders and is given the advantage of expelling jinn from the human body (rukiah).